Short- But Not Long-Term Effects of Creep Feeding Provided to Suckling Piglets - María Romero; Ana Heras-Molina; María Muñoz; Luis Calvo; José Ignacio Morales; Ana Isabel Rodríguez; Rosa Escudero; Clemente López-Bote; Cristina Óvilo; Álvaro Olivares (Animals)
Fifty-eight litters (16 from primiparous gilts and 42 from multiparous sows) were used, with a total number of 750 piglets involved in the study. Birth weight was stratified into three groups: low (<1.02 kg; LBW), normal (1.02–1.62 kg; NBW), and high (>1.62 kg; HBW). A creep feeding diet was offered to piglets in a creep feeder in 29 litters from day 7 until their weaning. Piglet mortality was recorded daily. Traceability was ensured up to the point of carcass splitting and subsequent meat analysis. Each carcass was eviscerated and weighed individually. Sixty-nine piglets were selected for the microbiome analysis (35 from the control group and 34 from the creep feeding group). Feces samples from the rectum were obtained at three time points (three days prior weaning, a week after weaning, and before the slaughtering of the pigs). Mortality during lactation was influenced by birth weight, with LBW piglets exhibiting a six-fold higher mortality rate than HBW. Creep feeding did not impact piglet mortality. Heavier piglets demonstrated greater weight gain when subjected to creep feeding, while the growth potential of lighter piglets was reduced. Variation in creep feeding consumption based on birth weight also affected microbiome composition, with high-birth-weight piglets displaying higher alpha diversity than low- and normal-birth-weight piglets seven days after lactation. Alpha diversity is indicative of gut health, with higher values suggesting greater stability and adaptability to different feed sources. In conclusion, the immediate impacts of creep feeding appear to be most prominent during lactation and potentially early postweaning. These short-term effects are modulated by birth weight, with HBW piglets demonstrating the greatest benefits from the implementation of creep-feeding practices.